Porous mullite ceramic with spinel pore layer structure and preparation method of porous mullite ceramic

By introducing a spinel pore layer structure into porous mullite ceramics and using lightweight spherical mullite powder and fused magnesia/starch composite pore-forming agent, the problem of mullite ceramics' resistance to alkali metal compounds at high temperatures has been solved. The problem of insufficient corrosion ability is achieved, and higher alkali corrosion resistance and comprehensive performance are achieved.

CN119330744AActive Publication Date: 2025-01-21HUNAN HUAXIN NEW MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411460663.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

Mullite ceramics have poor resistance to alkali metal compounds at high temperatures, resulting in corrosion damage to the working surface layer of the material.

Method used

The preparation method of porous mullite ceramics with spinel pore layer structure includes using light spherical mullite powder, sintered corundum powder, silica powder and fused magnesite/starch composite pore-forming agent as raw materials, and passing Roasting forms a spinel pore layer structure.

Benefits of technology

It improves the corrosion resistance of alkali metal compounds of ceramics and shows the comprehensive advantages of porosity, compressive strength and low thermal conductivity. Compared with porous mullite ceramics without a spinel pore layer, the corrosion resistance of soda ash is improved by 18.4 to 31.8 %.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330744A_ABST
    Figure CN119330744A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramics, in particular to a porous mullite ceramic with a spinel pore layer structure and a preparation method of the porous mullite ceramic. According to the preparation method of the porous mullite ceramic with the spinel pore layer structure, light spherical mullite micro powder, sintered corundum micro powder, silicon micro powder and a fused magnesite / starch (MgO (at) (C6H10O5) n) composite pore-forming agent are taken as raw materials, a binding agent is added for mixing, packaging and ageing are performed, mechanical pressing, drying and roasting are performed, and the porous mullite ceramic with the spinel pore layer structure is obtained. The preparation method has the characteristics of low preparation cost, simple process and controllable process; the prepared porous mullite ceramic with the spinel pore layer structure is small in volume density, low in thermal conductivity, high in compression strength and excellent in alkali metal compound erosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, and in particular to a porous mullite ceramic with a spinel pore layer structure and a preparation method thereof. Background Art

[0002] Porous ceramics can increase the specific surface area of ​​materials and reduce the thermal conductivity of materials due to the presence of a large number of closed or through pores in their internal structure. They are widely used in fields such as filtration, catalyst carriers, and thermal insulation materials. Among them, mullite porous ceramics have excellent high temperature resistance, thermal shock stability, and mechanical strength, which ensure the durability and reliability of the material in practical applications. However, mullite has poor resistance to erosion by alkali metal compounds (R, R2O, ROH, etc., where R is Li, Na, K) at high temperatures. Alkali or its salts usually diffuse into the material in liquid or gaseous state, react with it, and expand in volume, resulting in erosion of the working surface of the material. Among them, the erosion rate of alkali or its salts is related to the number and size of pores in mullite. Therefore, porous mullite with high porosity and low thermal conductivity is limited in practical applications.

[0003] As in (Li Guangqi, Chen Junhong, Jia Yuanping, et al. Damage Mechanism of Silicon Carbidemullite Bricks for Transition Zone of Cement Rotary Kilns[J]. China , s Refractories, 2020, 29(4):35-39) mentioned that in the transition zone of the cement rotary kiln converter, alkaline vapor will enter the internal pores of the silicon carbide-mullite brick body, forming a high-temperature liquid phase zone, dissolving Al2O3 and SiO2 in the brick, and the precipitated potassium feldspar, potassium chloride and other crystals will destroy the original structure of the brick body, increase the difference in thermal expansion coefficient between the high-temperature dense end and the metamorphic layer, and cause cracks to form in the brick body and cause spalling.

[0004] Domestic and foreign scholars have conducted a lot of research on the problem of poor resistance to alkali metal compound corrosion of aluminum-silicon materials represented by mullite. A common method is to introduce alkaline refractory materials such as magnesium, magnesium spinel, dolomite, forsterite, and limestone into the material system. For example, in the article (Wang Ruining. Preparation and Performance Research of Mullite-Spinel High-Temperature Materials [D]. Xi'an University of Architecture and Technology, 2005.), mullite and magnesium aluminum spinel are uniformly mixed and sintered, hoping to use the excellent corrosion resistance of magnesium aluminum spinel to improve the overall corrosion resistance of the composite material. It is worth noting that since the introduced spinel phase is in a free state, alkali metal compounds will still react with mullite first, so that the alkali corrosion resistance of the material system is improved, but not significantly improved. Summary of the invention

[0005] The object of the present invention is to provide a porous mullite ceramic with a spinel pore layer structure and excellent resistance to erosion by alkaline compounds and a preparation method thereof in view of the above-mentioned deficiencies in the prior art.

[0006] The invention discloses a method for preparing a porous mullite ceramic with a spinel pore layer structure, comprising: preparing a porous mullite ceramic with a spinel pore layer structure by using light spherical mullite micropowder, sintered corundum micropowder, silicon micropowder, fused magnesia sand / starch (MgO@(C6H 10 O5) n) using a composite pore-forming agent as a raw material, adding a binder to the mixture, encapsulating the trapped material, machine pressing, drying, and calcining to obtain a porous mullite ceramic with a spinel pore layer structure; Wherein, the fused magnesia / starch (MgO@(C6H 10 The preparation method of the composite pore-forming agent is as follows: a mixed gel is prepared by using starch, fused magnesia and water, and the mixed gel is dried and ball-milled to a particle size of less than 0.074 mm to obtain the composite pore-forming agent; The light spherical mullite powder is obtained by crushing, drying, grinding, granulating and high-temperature calcining secondary bauxite.

[0007] Furthermore, light spherical mullite powder, sintered corundum powder, silicon powder, fused magnesia / starch (MgO@(C6H 10 O5)n) The mass ratio of the composite pore-forming agent is 40-60:20-40:6-10:8-18.

[0008] Furthermore, aluminum dihydrogen phosphate solution is used as a binder, and aluminum dihydrogen phosphate solution is 8 to 10 wt % of the raw material.

[0009] Furthermore, the calcination is carried out at 1350-1450° C. for 3-4 hours.

[0010] Furthermore, the fused magnesia / starch (MgO@(C6H 10O5)n) The preparation process of the composite pore-forming agent is specifically as follows: starch, fused magnesia and water are mixed in a mass ratio of 1: (0.8-1.6): (2.5-4), the mixture is placed in a constant temperature magnetic stirring water bath for heating and stirring, and when the temperature rises to 70-75°C, it is allowed to stand for 1-1.5 hours to obtain a mixed gel, the gel is cooled to room temperature, and dried at 100-110°C for 12-24 hours. The dried material is ball-milled to a particle size less than 0.074 mm to obtain a composite pore-forming agent.

[0011] Furthermore, the ball milling medium is corundum balls, and the ball-to-material ratio is 3:1 to 5:1.

[0012] Furthermore, the starch is any one of corn starch, sweet potato starch or cassava starch amylopectin.

[0013] Furthermore, the specific preparation method of the lightweight spherical mullite powder is as follows: secondary bauxite is crushed to 30-90 mm, dried in a dryer, ground to 200-400 mesh, granulated by a granulator, placed in a rotary kiln at 1400-1500° C. to calcine into mature material, and sieved to obtain lightweight spherical mullite of various particle sizes.

[0014] Furthermore, the main chemical components of the fused magnesia are: MgO content ≥ 95.03wt%, Al2O3 content ≤ 0.18wt%, SiO2 content ≤ 1.65wt%; and the particle size of the fused magnesia is ≤ 0.074mm.

[0015] Furthermore, the main chemical components of the lightweight spherical mullite powder are: Al2O3 content ≥62.29wt%, SiO2 content ≥30.8wt%, and MgO content ≤0.3wt%.

[0016] Furthermore, the lightweight spherical mullite powder has a particle size of ≤0.074 mm, an apparent porosity of 29.1%, and a median pore diameter of 10.30 μm.

[0017] Furthermore, the main chemical components of the sintered corundum powder are: Al2O3 content ≥ 99.46wt%, SiO2 content ≤ 0.09wt%; and the particle size of the sintered corundum powder ≤ 0.074mm.

[0018] The main chemical components of the silicon micropowder are: SiO2 content ≥96.11wt%, Al2O3 content ≤0.51wt%, MgO content ≤0.25wt%; the particle size of the silicon micropowder is ≤0.109mm.

[0019] A porous mullite ceramic with a spinel pore layer structure prepared by the above preparation method.

[0020] Compared with the prior art, the present invention has the following advantages: 1. The present invention utilizes the gelatinization and aging characteristics of amylopectin to prepare a core-shell structured fused magnesia / starch (MgO@(C6H 10 O5)n) Composite pore forming agent, the shell layer (starch) will burn away to form pores during the pore forming process, and the exposed core (fused magnesia) will react with the pore wall (mullite) to form a magnesium-aluminum spinel pore layer structure (such as Figure 2 By adjusting the composite ratio of magnesia sand / starch in the composite pore-forming agent, the controllable design of the pore structure (magnesium aluminum spinel pore layer thickness, size and distribution, etc.) in the ceramic can be achieved.

[0021] 2. The lightweight spherical mullite powder used in the present invention is a functional refractory raw material. The spherical geometry gives the powder good fluidity, controllable particle size and tight stacking characteristics; inside the spherical powder there is a grid formed by cross-stacked columnar mullite, and the surface of the grid is covered with a certain amount of glass phase, so that a large number of tiny closed pores are formed inside the powder. Compared with traditional raw materials such as alumina, mullite, and alumina, porous mullite ceramics prepared with lightweight spherical mullite powder as the main raw material have the advantages of light weight, low conductivity and high strength.

[0022] 3. The present invention utilizes fused magnesia / starch (MgO@(C6H 10 O5)n) The structure and chemical composition characteristics of the composite pore-forming agent. In the process of preparing porous mullite ceramics by organic combustion method, fused magnesia reacts with free alumina at high temperature to form pores with magnesia-alumina spinel pore layer structure (such as Figure 2 As shown). Due to the good resistance of spinel to alkali metal compound corrosion, the existence of spinel shell structure can solve the problem that when the free spinel phase is directly introduced into the mullite material, the aluminum-silicon bonding phase will still react with the alkali first and it is difficult to prevent the penetration of the alkali.

[0023] 4. Due to the difference in thermal expansion coefficients between spinel and mullite, microcracks will form at the interface between the spinel pore layer and the mullite matrix in the porous ceramics prepared by the present invention. By adjusting the amount of silicon micropowder added in the raw material and utilizing the high glass phase of lightweight spherical mullite micropowder, the microcracks can be effectively sealed and regulated to form a collection of closed pores. Compared with the composite ceramics prepared by the traditional spinel and mullite mechanical mixing method, the problems caused by cracks, visible pores, through pores, etc. are weakened, and the strength and alkali corrosion resistance of the porous mullite are improved.

[0024] The porous mullite ceramic with a spinel pore layer structure prepared by the present invention is tested to have a volume density of 1.01 to 2.09 g·cm -3; The apparent porosity is 32.5-56.1%; the compressive strength is 58.5-91.1 MPa; the thermal conductivity is 0.21-0.47 W / (m·K); the soda ash corrosion resistance is improved by 18.4-31.8% compared with the porous mullite ceramics without spinel pore layer.

[0025] Therefore, the present invention has the characteristics of low preparation cost, simple process and controllable process; the prepared porous mullite ceramic with spinel pore layer structure has small volume density, low thermal conductivity, high compressive strength and excellent resistance to alkali metal compound corrosion. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a SEM image of the porous mullite ceramic with a spinel pore layer structure prepared in Example 1; Figure 2 This is a schematic diagram of the structure of the porous mullite ceramic with a spinel pore layer structure prepared in Example 1. DETAILED DESCRIPTION

[0027] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0028] Fused magnesia / starch (MgO@(C6H 10 O5)n) Preparation of composite pore-forming agent The ingredients are prepared according to the mass ratio of starch, fused magnesia and water of 1: (0.8-1.6): (2.5-4), and the mixture is placed in a constant temperature magnetic stirring water bath for heating and stirring. When the temperature rises to 70-75°C, the mixture is allowed to stand for 1 hour to allow the starch to gelatinize, thereby obtaining a mixed gel of starch and fused magnesia. After the gel is cooled and aged, it is dried at 100-110°C for 12-24 hours. After drying, the material is ball-milled to a particle size of less than 0.074 mm to obtain a composite pore-forming agent.

[0029] The main chemical components of fused magnesia are: MgO content ≥95.03wt%, Al2O3 content ≤0.18wt%, SiO2 content ≤1.65wt%; the particle size of fused magnesia is ≤0.074mm.

[0030] The starch is any one of corn starch, sweet potato starch or tapioca starch amylopectin.

[0031] Preparation of the lightweight spherical mullite powder Secondary bauxite is crushed to 30-90mm, dried in a dryer, ground to 200-400 mesh, granulated by a granulator, calcined in a rotary kiln at 1400-1500℃ to become clinker, and sieved to obtain lightweight spherical mullite of various particle sizes.

[0032] The main chemical components of the light spherical mullite powder are: Al2O3 content ≥62.29wt%, SiO2 content ≥30.8wt%, MgO content ≤0.3wt%; the particle size of the light spherical mullite powder is ≤0.074mm, the apparent porosity is 29.1%, and the median pore diameter is 10.30μm.

[0033] Preparation of Porous Mullite Ceramics with Spinel Porous Layer Structure The invention adopts 40-60wt% of light spherical mullite powder, 20-40wt% of sintered corundum powder, 6-10wt% of silicon powder and 8-18wt% of composite pore-forming agent as raw materials, and adds 8-10wt% of aluminum dihydrogen phosphate solution of the raw materials as a binder. The materials are mixed for 60-120min, packaged for 12-24h, pressed at 80-120MPa, dried at 90-110℃ for 12-24h, and kept at 1350-1450℃ for 3-4h to obtain a porous mullite ceramic with a spinel pore layer structure.

[0034] The main chemical components of sintered corundum powder are: Al2O3 content ≥99.46wt%, SiO2 content ≤0.09wt%; the particle size of sintered corundum powder ≤0.074mm.

[0035] The main chemical components of silicon micropowder are: SiO2 content ≥96.11wt%, Al2O3 content ≤0.51wt%, MgO content ≤0.25wt%; the particle size of silicon micropowder ≤0.109mm.

[0036] Example 1 Firstly, starch, fused magnesia and water were prepared in a mass ratio of 1:0.9:2.6. The mixture was placed in a constant temperature magnetic stirring water bath for heating and stirring. When the temperature rose to 70°C, it was allowed to stand for 1 hour to allow the starch to gelatinize to obtain a mixed gel. After the gel was cooled and aged, it was dried at 100°C for 12 to 15 hours. After drying, the material was ball-milled to a particle size less than 0.074 mm to obtain a composite pore-forming agent.

[0037] Then, light spherical mullite powder, sintered corundum powder, silicon powder, fused magnesia / starch (MgO@(C6H 10 O5)n) A composite pore-forming agent is used as a raw material, and 8wt% of aluminum dihydrogen phosphate solution of the raw material is added as a binder, the materials are mixed for 60 to 90 minutes, the materials are packaged for 12 to 15 hours, and the materials are pressed at 80 to 90 MPa. The materials are dried at 90 to 100°C for 12 to 15 hours, and kept at 1350 to 1400°C for 3 to 3.5 hours to obtain a porous mullite ceramic with a spinel pore layer structure.

[0038] The porous mullite ceramic with a spinel pore layer structure prepared in this embodiment was tested: the volume density was 2.09 g·cm -3 ; The apparent porosity is 32.5%; the compressive strength is 58.5 MPa; the thermal conductivity is 0.47 W / (m·K); the soda ash erosion resistance is 40.17%, which is 18.4% higher than that of the porous mullite ceramic without spinel pore layer prepared in Comparative Example 1.

[0039] Example 2 Firstly, starch, fused magnesia and water were prepared in a mass ratio of 1:1.1:3.0, and the mixture was placed in a constant temperature magnetic stirring water bath for heating and stirring. When the temperature rose to 70°C, the mixture was allowed to stand for 1 hour to allow the starch to gelatinize to obtain a mixed gel. After the gel was cooled and aged, it was dried at 100°C for 15 to 18 hours. After drying, the material was ball-milled to a particle size less than 0.074 mm to obtain a composite pore-forming agent.

[0040] Then, light spherical mullite powder, sintered corundum powder, silicon powder, fused magnesia / starch (MgO@(C6H 10 O5)n) composite pore-forming agent, adding 8-9wt% aluminum dihydrogen phosphate solution of the raw material as a binder, mixing for 60-90 minutes, encapsulating and trapping the material for 15-18 hours, pressing and molding at 90-100MPa, drying at 90-100℃ for 15-18 hours, and keeping warm at 1350-1400℃ for 3-3.5 hours to obtain a porous mullite ceramic with a spinel pore layer structure.

[0041] The porous mullite ceramic with a spinel pore layer structure prepared in this embodiment was tested to have a volume density of 1.65 g·cm -3 The apparent porosity is 40.75%; the compressive strength is 69.9 MPa; the thermal conductivity is 0.35 W / (m·K); the soda ash erosion resistance is 38.81%, which is 22.5% higher than that of the porous mullite ceramic without spinel pore layer prepared in Comparative Example 1.

[0042] Example 3 A porous mullite ceramic with a spinel pore layer structure and a preparation method thereof. The preparation method described in this embodiment is: Firstly, starch, fused magnesia and water were prepared in a mass ratio of 1:1.3:3.5. The mixture was placed in a constant temperature magnetic stirring water bath for heating and stirring. When the temperature rose to 75°C, it was allowed to stand for 1.5 hours to allow the starch to gelatinize to obtain a mixed gel. After the gel was cooled and aged, it was dried at 110°C for 18 to 21 hours. After drying, the material was ball-milled to a particle size less than 0.074 mm to obtain a composite pore-forming agent.

[0043] Then, light spherical mullite powder, sintered corundum powder, silicon powder, fused magnesia / starch (MgO@(C6H 10 O5)n composite pore-forming agent is used as raw material, and 10wt% of aluminum dihydrogen phosphate solution of the raw material is added as a binder, the materials are mixed for 90-120 minutes, the materials are packaged for 18-21 hours, and the materials are pressed into shape at 100-110MPa. The materials are dried at 100-110°C for 18-21 hours, and kept warm at 1400-1450°C for 3.5-4 hours to obtain a porous mullite ceramic with a spinel pore layer structure.

[0044] The porous mullite ceramic with a spinel pore layer structure prepared in this embodiment was tested: the volume density was 1.54 g·cm -3 The apparent porosity is 44.4%. The compressive strength is 75.6 MPa. The thermal conductivity is 0.31 W / (m·K). The soda ash corrosion resistance is 37.01%, which is 28.5% higher than that of the porous mullite ceramic without spinel pore layer prepared in Comparative Example 1.

[0045] Example 4 A porous mullite ceramic with a spinel pore layer structure and a preparation method thereof. The preparation method described in this embodiment is: Firstly, starch, fused magnesia and water were prepared in a mass ratio of 1:1.5:3.8. The mixture was placed in a constant temperature magnetic stirring water bath for heating and stirring. When the temperature rose to 75°C, it was allowed to stand for 1.5 hours to allow the starch to gelatinize to obtain a mixed gel. After the gel was cooled and aged, it was dried at 110°C for 21 to 24 hours. After drying, the material was ball-milled to a particle size less than 0.074 mm to obtain a composite pore-forming agent.

[0046] Then, light spherical mullite powder, sintered corundum powder, silicon powder, fused magnesia / starch (MgO@(C6H 10 O5)n composite pore-forming agent, adding 10wt% aluminum dihydrogen phosphate solution of the raw material as a binder, mixing for 90-120min, encapsulating and trapping the material for 21-24h, pressing and molding at 110-120MPa, drying at 100-110°C for 21-24h, and keeping warm at 1400-1450°C for 3.5-4h to obtain a porous mullite ceramic with a spinel pore layer structure.

[0047] The porous mullite ceramic with a spinel pore layer structure prepared in this embodiment was tested: the volume density was 1.01 g·cm -3 The apparent porosity is 56.1%. The compressive strength is 91.1 MPa. The thermal conductivity is 0.21 W / (m·K). The soda ash corrosion resistance is 35.79%, which is 31.8% higher than that of the porous mullite ceramic without spinel pore layer prepared in Comparative Example 1.

[0048] Comparative Example 1 In addition to the use of starch (non-electrofused magnesia / starch (MgO@(C6H 10 O5) n) composite pore-forming agent), and the rest are the same as in Example 1.

[0049] The porous mullite ceramic prepared in this comparative example 1 was tested: the volume density was 2.79 g·cm -3 ; The apparent porosity is 28.9%; the compressive strength is 57.3MPa; the thermal conductivity is 0.44 W / (m·K); and the soda ash corrosion resistance is 47.56%.

[0050] Table 1

[0051] Figure 1 The SEM image of the porous mullite ceramic with a spinel pore layer structure prepared in Example 1 and Table 1 are EDS analysis. It can be seen that the inner surface layer of the "pores" in the ceramic is a magnesium-aluminum spinel layer, and the ceramic matrix is ​​a mullite phase. This means that the "pores" inside the porous mullite ceramic have the characteristics of a spinel pore layer structure.

[0052] For matters not mentioned above, the prior art applies.

[0053] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a porous mullite ceramic with a spinel pore layer structure, characterized in that: Lightweight spherical mullite powder, sintered corundum powder, silica powder, fused magnesia / starch (MgO@(C6H 10 O5) n) using a composite pore-forming agent as a raw material, adding a binder to the mixture, encapsulating the trapped material, machine pressing, drying, and calcining to obtain a porous mullite ceramic with a spinel pore layer structure; Wherein, the fused magnesia / starch (MgO@(C6H 10 O5)n) The preparation method of the composite pore-forming agent is as follows: a mixed gel is prepared by using starch, fused magnesia and water, and the mixed gel is dried and ball-milled to a particle size of less than 0.074 mm to obtain the composite pore-forming agent; The light spherical mullite powder is obtained by crushing, drying, grinding, granulating and high-temperature calcining secondary bauxite.

2. The preparation method according to claim 1, characterized in that: Lightweight spherical mullite powder, sintered corundum powder, silica powder, fused magnesia / starch (MgO@(C6H 10 O5)n) The mass ratio of the composite pore-forming agent is 40-60:20-40:6-10:8-18.

3. The preparation method according to claim 1, characterized in that: Aluminum dihydrogen phosphate solution is a binder, and the aluminum dihydrogen phosphate solution is 8-10wt% of the raw material.

4. The preparation method according to claim 1, characterized in that: The calcination is carried out at 1350-1450℃ for 3-4h.

5. The preparation method according to claim 1, characterized in that: The fused magnesia / starch (MgO@(C6H 10 O5)n) The preparation process of the composite pore-forming agent is specifically as follows: starch, fused magnesia and water are mixed in a mass ratio of 1:(0.8-1.6):(2.5-4), the mixture is placed in a constant temperature magnetic stirring water bath for heating and stirring, and when the temperature rises to 70-75°C, it is allowed to stand for 1-1.5 hours to obtain a mixed gel, the gel is cooled to room temperature, and dried at 100-110°C for 12-24 hours. The dried material is ball-milled to a particle size of less than 0.074 mm to obtain a composite pore-forming agent.

6. The preparation method according to claim 1, characterized in that: The starch is any one of branched-chain starches such as corn starch, sweet potato starch or cassava starch.

7. The preparation method according to claim 1, characterized in that: The specific preparation method of the light spherical mullite powder is as follows: secondary bauxite is crushed to 30-90 mm, dried in a dryer, ground to 200-400 mesh, granulated in a granulator, placed in a rotary kiln at 1400-1500° C. and calcined to obtain mature material, and sieved to obtain light spherical mullite of various particle sizes.

8. The preparation method according to claim 1, characterized in that: The main chemical components of the fused magnesia are: MgO content ≥ 95.03wt%, Al2O3 content ≤ 0.18wt%, SiO2 content ≤ 1.65wt%; the particle size of the fused magnesia is ≤ 0.074mm; The main chemical components of the lightweight spherical mullite powder are: Al2O3 content ≥ 62.29wt%, SiO2 content ≥ 30.8wt%, MgO content ≤ 0.3wt%; The light spherical mullite powder has a particle size of ≤0.074 mm, an apparent porosity of 29.1%, and a median pore diameter of 10.30 μm.

9. The preparation method according to claim 1, characterized in that: The main chemical components of the sintered corundum micropowder are: Al2O3 content ≥ 99.46wt%, SiO2 content ≤ 0.09wt%; the particle size of the sintered corundum micropowder ≤ 0.074mm; The main chemical components of the silicon micropowder are: SiO2 content ≥ 96.11wt%, Al2O3 content ≤ 0.51wt%, MgO content ≤ 0.25wt%; the particle size of the silicon micropowder is ≤ 0.109mm.

10. A porous mullite ceramic with a spinel pore layer structure prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of porous high-strength mullite refractory raw material

    CN109111236A

  • Preparation method of porous ceramic with in-situ generated magnesium aluminate spinel whisker skeleton

    CN110452009A

  • Preparation method of mullite porous ceramic

    CN111302773A

  • Mullite micro-nano pore heat insulation refractory material and preparation method thereof

    CN114133258A

  • High temp. porous ceramic bodies mfr. - by heating mullite, corundum, spinel or graphite with starch, cellulose or other hydrocarbon as binder

    DE4104449A1